Trauma, Aggression, and Post Conflict Perpetration of Community Violence in Female Former Child Soldiers—A Study in Eastern DR Congo - Robjant, Katy; Schmitt, Sabine; Chibashimba, Amani; Carleial, Samuel; Elbert, Thomas; Koebach, Anke (Frontiers in Psychiatry, 2020)
Abstract Objective: Former combatants are exposed to multiple traumatic stressors during conflict situations, and usually participate in perpetration of violence. Ongoing perpetration of violence in post conflict areas, linked to mental health problems and appetitive aggression, destabilises peace keeping efforts. The aim of this study is to investigate lifetime exposure to violence and the relationship between this exposure and mental health and current violent behaviour in a sample of female former child soldiers with a history of perpetration of violence in Eastern DR Congo. Methods: 98 female former child soldiers who had been abducted and forcibly recruited during the M23 insurgency (2012-2014) were assessed for lifetime exposure to trauma including perpetration of violence, clinical outcomes (PTSD and appetitive aggression) and current violent behaviour Results: Female former child soldiers had been exposed to extremely high levels of trauma including perpetration of violence and presented with high levels of mental health problems. Linear regression models showed that current violent behaviour was predicted by both PTSD and appetitive aggression. Conclusions: Trauma exposure predicts ongoing perpetration of violence post conflict via the resulting mental health problems. The findings imply that if PTSD and appetitive aggression symptoms are successfully treated, ongoing violent behaviour in the community post conflict will also decrease. .